Semen reactive oxygen species levels are correlated with erectile function among chronic prostatitis/chronic pelvic pain syndrome patients - YÜKSEL, MERAL (NATURE PUBLISHING GROUP, 2018)
Chronic Prostatitis/Chronic Pelvic Pain Syndrome (CP/CPPS) is often associated with erectile dysfunction (ED). However, the underlying pathophysiological mechanisms of ED occurrence are still unclear in patients with CP/CPPS. The aim of the study was to investigate superoxide anion (O-2(center dot-)) and total reactive oxygen species (ROS) production in semen of men with category IIIA CP/CPPS and their association with ED. This prospective study included 33 men with category IIIA CP/CPPS. Control group consisted of 13 healthy men. Total ROS and O-2(center dot-) production were assayed by luminol and lucigenin-dependent chemiluminescence (CL) methods, respectively. ED was evaluated using the IIEF-5 questionnaire. Patients with CP/CPPS had significantly higher seminal total ROS and O-2(center dot-) levels than healthy control subjects (2.9 +/- 0.5 relative light unit (RLU) vs. 2.4 +/- 0.2 RLU, p < 0.001; luminol-dependent CL and 2.5 +/- 0.4 RLU vs. 2.3 +/- 0.2 RLU, p = 0.02; lucigenin-dependent CL, respectively). Seminal O-2(center dot-) and ROS levels were negatively correlated with IIEF-5 scores (r = -0.556, r = -0.536; p < 0.001, respectively). These results may suggest O-2(center dot-)/ROS overproduction could be one of the important mechanisms in the etiology of ED development in CP/CPPS patients.
Keywords: INSTITUTES-OF-HEALTH; INTERNATIONAL INDEX; OXIDATIVE STRESS; NADPH OXIDASES; SEMINAL PLASMA; NITRIC-OXIDE; DYSFUNCTION; MEN; CLASSIFICATION; SPERMATOZOA